'La doble condición': landmine victims, forced displacement, and disability in Colombia's Magdalena Medio. (19th May 2018) - Counter, Max
Abstract: The small body of scholarship that examines the intersection between forced displacement and physical disability draws important attention to the material difficulties simultaneously disabled and displaced people experience. Instead of focusing on disability as a condition lived against the spatial backdrop of forced displacement, this paper approaches disability and displacement as mutually referential spatial conditions. Based on fieldwork with internally displaced landmine victims in Colombia's Magdalena Medio region, this research highlights how the intersection between physical impairment and forced displacement produces both disabling spatial imaginaries of fear as well as painfully embodied rhythms of daily life. Nonetheless, this paper draws attention to urban agricultural projects' enabling potential to produce grounding rhythms of labor for landmine victims. Finally, this paper suggests that contexts of forced displacement require close consideration of spatial imaginaries of fear as well as experiences of direct structural violence as key factors underpinning the social production of disability.